Evaluation of the Biostimulant Activity of Zaxinone Mimics (MiZax) in Crop Plants - Wang, Jian You; Jamil, Muhammad; Hossain, Md. Golap; Chen, Guan-Ting Erica; Berqdar, Lamis; Ota, Tsuyoshi; Blilou, Ikram; Asami, Tadao; Al-Solimani, Samir Jamil; Mousa, Magdi Ali Ahmed; Al-Babili, Salim (Frontiers in Plant Science, 2022)
Global food security is a critical concern that needs practical solutions to feed the expanding human population. A promising approach is the employment of biostimulants for increasing crop production. Biostimulants include compounds that boost plant growth and performance. Recently, the apocarotenoid zaxinone and its mimics (MiZax) were shown to have a promising growth-promoting effect in rice under lab conditions. In the present study, we investigated the effect of MiZax on the growth and yield of three dicot horticultural plants (tomato, capsicum, and squash) in different growth environments, as well as on the growth and development of the monocot date palm, an important crop in the Middle East. The application of MiZax significantly enhanced plant height, flower and branch numbers, fruit size, and total fruit yield in independent field trials from 2020 to 2021. Importantly, the amount of applied MiZax was far less than that used with the commercial compound humic acid. Our results indicate that MiZax have significant application potential to improve the performance and productivity of horticultural crops.